Perilaku Heuristik, Persepsi Risiko, dan Preferensi Risiko : Determinan Keputusan Investasi - Tisna Kusuma Rahayu; Ririh Dian Pratiwi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The phenomenon of increasing investment interest among the younger generation has not been fully matched by the ability to control heuristic behavior and manage risk adequately and sustainably. This research investigates how heuristic behavior, risk perception, and risk preference influence investment decision-making among students participating in capital market study groups at universities in Semarang City. The sample consisted of 191 students who were chosen through a proportionate stratified random sampling technique. Data were processed by means of SPSS version 25. The findings show that heuristic behavior and risk perception have a positive and significant effect on investment decisions, while risk preference has no significant effect. The practical implications of this study are relevant for young investors, educational institutions, and regulators in improving the quality of investment decision making, and it also serves as a reference for future research.